A Child-Driven Metadata Schema: A Holistic Analysis of Children's Cognitive Processes During Book Selection - (:unkn) unknown (My University, 2014)
The purpose of this study was to construct a child-driven metadata schema by understanding children's cognitive processes and behaviors during book selection. Existing knowledge organization systems including metadata schemas and previous literature in the metadata domain have shown that there is a no specialized metadata schema that describes children's resources that also is developed by children. It is clear that children require a new or alternative child-driven metadata schema. Child-driven metadata elements reflected the children's cognitive perceptions that could allow children to intuitively and easily find books in an online cataloging system. The literature of development of literacy skills claims that the positive experiences of selecting books empower children's motivation for developing literacy skills. Therefore, creating a child-driven metadata schema not only contributes to the improvement of knowledge organization systems reflecting children's information behavior and cognitive process, but also improves children's literacy and reading skills. Broader research questions included what metadata elements do children like to use? What elements should a child-driven metadata schema include? In order to answer these research questions, a triangulated qualitative research design consisting of questionnaires, paired think-aloud, interview, and diaries were used with 22 child participants between the ages of 6 and 9. A holistic understanding of the children's cognitive processes during book selection as a foundation of a child-driven metadata schema displays an early stage of an ontological contour for a children's knowledge organization system. A child-driven metadata schema constructed in this study is apt to include different metadata elements from those metadata elements existing in current cataloging standards. A child-driven metadata schema includes five classes such as story/subject, character, illustration, physical characteristics, and understandability, and thirty three metadata elements such as character's names and images, book cover's color, shape, textured materials, engagement element, and tone. In addition, the analysis of the relationship between emergent emotional vocabularies and cognitive factors and facets illustrated the important role of emotion and attention in children's information processing and seeking behaviors.
Keywords: Children's Cognitive Processes; Children's Digital Libraries; Children's Information Seeking Behaviors; Emotion; Knowledge Organization; Metadata